The biblical meaning of Ekklesia and Its relevance with the christian church - Rashid, Ungaran (IIUM Press, 2020)
The topic on the church is one of important issues in the systematic theology in Christianity. The Christians believe that all of them gathered together by God in an institution named church, which mostly refers to a building or organization. On the other hand, the Scriptures mention that Jesus (PBUH) will build and become the head of the ekklesia, which refers to a community. This community contains people who believe and confess that Jesus (PBUH) is the Messiah, regardless of an institution or organization. This article tries to examine the relevance between the ekklesia of Jesus (PBUH) and the Christian Church by comparing the two in terms of definition, characteristics, and government. The aim of this article is to examine either the Christian Church is still in accord with the concept of ekklesia or there are various differences so that the Church is no longer in accordance with the Biblical studies.